Constructing life: old troubles, new challenges for Psychology - Duarte, Maria Eduarda (2018)
This article is focused on the study object of the developmental psychology and career management field, within the context of organizations, and it is analyzed on an historical perspective. The second part revolves around the scientific tools that seek to match the individuals’ needs with the organizations’. In the third part, the principles of life construction paradigm are considered.